2021
DOI: 10.1002/ece3.7777
|View full text |Cite
|
Sign up to set email alerts
|

Fine‐scale movements and behaviors of coyotes (Canis latrans) during their reproductive period

Abstract: This is an open access article under the terms of the Creat ive Commo ns Attri bution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 78 publications
(155 reference statements)
3
10
0
Order By: Relevance
“…Coyotes selected areas of increased vegetation density during spring and winter revisitations, while avoiding areas of high vegetative density during the summer. Selection for areas with dense vegetation during spring was also observed in an independent study of coyote movements in north‐central Georgia, approximately 125 and 275 km from our SRA and Alabama study areas, respectively (Chamberlain et al, 2021). Using a behavioral state model, Chamberlain et al (2021) reported that resident coyotes selected areas with dense vegetation density when resting or foraging during the pup‐rearing season.…”
Section: Discussionsupporting
confidence: 73%
See 4 more Smart Citations
“…Coyotes selected areas of increased vegetation density during spring and winter revisitations, while avoiding areas of high vegetative density during the summer. Selection for areas with dense vegetation during spring was also observed in an independent study of coyote movements in north‐central Georgia, approximately 125 and 275 km from our SRA and Alabama study areas, respectively (Chamberlain et al, 2021). Using a behavioral state model, Chamberlain et al (2021) reported that resident coyotes selected areas with dense vegetation density when resting or foraging during the pup‐rearing season.…”
Section: Discussionsupporting
confidence: 73%
“…Selection for areas with dense vegetation during spring was also observed in an independent study of coyote movements in north‐central Georgia, approximately 125 and 275 km from our SRA and Alabama study areas, respectively (Chamberlain et al, 2021). Using a behavioral state model, Chamberlain et al (2021) reported that resident coyotes selected areas with dense vegetation density when resting or foraging during the pup‐rearing season. Therefore, it was not surprising to us that coyotes exhibited selection for dense vegetation during spring in our study for two reasons.…”
Section: Discussionsupporting
confidence: 73%
See 3 more Smart Citations